As (im)possibilidades de constituição da subjetividade no mundo do trabalho: reflexões sobre (des)sublimação no contexto educacional - CARLONI, Paola Regina (2010)
To build culture and socializing, the subject must abdicate their desire for instant gratification through sublimation. In a fragmented and administered society, this possibility is reduced and converted into desublimation, which is at the service of domination. Therefore, the purpose of this study is to understand the constitution of subjectivity in the working world and bring up the (im) possibilities of sublimation in the educational context. We start from this concept to understand who is the subject that is formed in this culture, since the subjectivity is composed by the sublimation. To this end, we carried out a literature and epistemological research, referenced by Critical Theory of the Frankfurt School, especially from the writings of Adorno, Horkheimer and Marcuse, and authors who hold this discussion, such as Freud, Marx and Kant. Guests to the historical moment of implementation and consolidation of capitalism, reinforced by the Enlightenment ideals of equality, liberty and fraternity and its contradictions, to understand the sense of subjectivity and what are its consequences in a administered society, structured by the cultural industry. The encouragement of consumerism and the transformation of labor into a commodity, capable of generating profit, directly affects education, which should consist of the possibility of libidinal energy channeling to building a more human civilization through sublimation. However, the work becomes alienated and man loses its universality by not recognizing themselves in this ontological category of constitution of individuals. The education, to follow the logic of capitalism, does not reach the goal of cultural formation, but becomes desublimation to transform knowledge into goods for immediate satisfaction. The discussion is not limited in this study. The objective of raising it does not close the issue. According to Adorno (2006), a ready answer about what to do can undermine the development of knowledge required for any transformation. The possibilities for change are precisely in the field of reflection and clarification, because they are the necessary subsidies for a conscious practice. This work fits within the research area Culture and Educational Processes, of the Graduate Program in Education, of Federal University of Goiás.